Canalis basilaris medianus: An anatomical study - S. Malakhov; A. Shmarhalov; H. El Falougy; P. Lukacikova; A. Polovinshchykov; O. El Hassoun; S. Polak (Elsevier, 2024)
Background: The clivus, a key skull base structure for neurosurgeons due to its proximity to brainstem areas, is formed by the fusion of two bones. A rare variation, the canalis basilaris medianus (CBM) or clival canal, can exist within the occipital bone. The clivus has a rich venous network, and the CBM's presence might be linked to veins or embryonic structures. Understanding the CBM is valuable for interpreting clival fractures and during neurosurgery. This study aimed to determine the frequency and morphometric parameters of the CBM. Material and methods: Fifty-nine dry adult skulls were selected for the investigation. Morphometric measures included establishing the diameters of the internal and external foramina of the CBM, the length of the canal, and its distance from the foramen magnum (FM), jugular tubercles, and lateral margins of the basilar part of the occipital bone. Results: Out of the 59 skulls investigated, only a single specimen contained the CBM. Thus, the frequency of canal presence in our sample was 0.59 %. The internal foramen of the CBM was located on the internal surface of the clivus, 4.03 mm anteriorly to the FM with a diameter of 2.84 mm. Further, the canal passed through the clivus and had its external foramen on the external surface of the clivus at 0.11 mm above the pharyngeal tubercle and its distance from the FM was 9.19 mm. The length of the CBM was established at 8.16 mm. Conclusion: The CBM is a rare variation of the basilar part of the occipital bone. Therefore, the possibility of the existence of this variation should be considered when analyzing CT and MRI images to avoid misinterpretation of their results and during surgical interventions in this area.